SAT0014 The mutated RNA splicing protein HNRNP-A3 is a novel autoantigen in systemic rheumatic diseases a link to warburg effect in RA. (15th June 2017) - Marklein, B; Hansson, M; Steiner, G; Burmester, G; Skriner, K
Abstract : Background: The present study was undertaken to investigate novel anti-hnRNPs autoantibodies in rheumatic diseases. Objectives: Novel mutated hnRNP A3 was cloned out of RA synovial tissue linking it directly to Warburg effect and lactate production in RA. Increased lactate production in RA synovia and tumors is klinked to alternative splicing process from PKM1 to PKM2 hnRNPs dependent. Methods: After immunobloting and 2D-gel-eletrophoresis of a semipurified hnRNP fraction two protein spots were sequenced and identified to be highly similar to hnRNPA3. The hnRNP A3 variants were cloned from RA synovial tissue, which identified the isoforms found on protein level. 3700 RA sera were screened for the presence of mutated anti-hnRNP A3 autoantibodies using recombinant proteins and peptides thereof. Binding of RNA to hnRNP A3 (MA3) and mutated citrullinated A3 peptides (MCA3) the epitope recognition was investigated. Expression of hnRNP A3 in synovial tissue was analysed by Results: Autoantibodies to MA3 protein were detected in 13% of RA (n=215) patients, in 9% SLE (n=154), in 27% of MCTD patients (n=44/10) and in less than 5% of 129 patients with other rheumatic disorders but not at all in healthy controls on immunoblot. When using renaturated MA3 on ELISA 22% of RA patients were detected and 87% of these patients had erosive arthritis. Same modification as in cancer cells were identified in synovial tissue and verified by MS and DNA sequencing. Using 2–3 citrullinated MCA3 peptides up to 81% of patients (n=150) with established and 67% (n=2926) of patients with an early RA with a specificity of 97% were detected. In early RA 27% and 25% in established RA of CCP2 negative and 93% of CCP2 positive patients were identified. By combining with the already established CCP2 and the new MCA3, 72% of early patients are positive. MCA3 autoantibodies predominantly occur (p<0.001) in an erosive, severe course of disease and approximately 60% of these patients receive a TNF alpha blocker within a year. MRL Lpr/lpr sera were hnRNP-A3 reactive and the antibody generation is Toll 7 and 9 dependent. Anti-hnRNP-A3-antibodies are directed to conformational RNA binding epitopes. Expression of hnRNP-A3 revealed the antigen to be overexpressed in RA synovial tissue. Conclusions: Mutated hnRNP-A3 is as a novel Toll7/9 dependent autoantigen in systemic rheumatic diseases. These mutated proteins are major components of RNA and DNA containing alternative splicing complexes leading to the Warburg effect and and autoantibodies predominantly occurre in an erosive, and severe courses of RA. Disclosure of Interest: None declared